Is it Time to Change Radiotherapy: The Dawning of Chronoradiotherapy?. Issue 5 (May 2019) - Harper, E.; Talbot, C.J.
Abstract: A minority of radiotherapy patients experience adverse reactions as a result of the inevitable irradiation of the surrounding healthy tissue. These reactions range in severity and affect the patient's quality of life, as well as being dose-limiting. If the patients most at risk of toxicity could be identified before radiotherapy, the treatment pathway, radiation dose or fractionation could be altered to reduce toxicity while maintaining efficacy. Previous research is described on how chemotherapy treatments could be improved through the delivery of drugs at specific times of the day ('chronomodulation') based on the circadian rhythm. More recently time-of-day effects have been investigated for radiotherapy, yielding complex results, but with some promise for genetic prediction of the optimal time for treatment. This would allow an almost cost-free modification to treatment that would reduce toxicity. Despite the increasing evidence for 'chronotherapy' for treating cancer, little work has looked into the potential mechanisms underlying the time-of-day effect, which potentially include differences in inflammation, cell cycle or hormones. This overview discusses the main findings from chronotherapy so far and comments on why elucidating the biological mechanisms relating radiotherapy toxicity to the circadian cycle warrants further investigation.